Sublingual nitroglycerin administration in coronary computed tomography angiography: a systematic review - Takx, Richard A. P.; Suchá, Dominika; Park, Jakob; Leiner, Tim; Hoffmann, Udo (European radiology, 2015)
To systematically investigate the literature for the influence of sublingual nitroglycerin administration on coronary diameter, the number of evaluable segments, image quality, heart rate and blood pressure, and diagnostic accuracy of coronary computed tomography (CT) angiography.